2014
DOI: 10.1371/journal.pone.0089371
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Weakness of Proximal Muscle Studied with Motor Cortical Mapping: A TMS Study

Abstract: Aging-related weakness is due in part to degeneration within the central nervous system. However, it is unknown how changes to the representation of corticospinal output in the primary motor cortex (M1) relate to such weakness. Transcranial magnetic stimulation (TMS) is a noninvasive method of cortical stimulation that can map representation of corticospinal output devoted to a muscle. Using TMS, we examined age-related alterations in maps devoted to biceps brachii muscle to determine whether they predicted it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 86 publications
1
19
0
Order By: Relevance
“…Biceps brachii, being a proximal large muscle, is especially important in founding subsequent recovery of the hand in neurologic populations (Kumar et al, 1989). However, based on present findings and previous evidence from our work and of others (Plow et al, 2013; Plow et al, 2014; van Kuijk et al, 2009; Brasil-Neto et al, 1992), it becomes clear that the variable nature of its MEPs renders test-retest measurements of its TMS metrics weakly reproducible. Nevertheless, choosing metrics that define its excitability and output in terms of intensity of TMS device (RMTs or supra-maximal MEP intensities) and/or spatial spread of excitability (COGs and hotspots) would serve as robust markers to longitudinally track recovery and prognosticate upper extremity function across populations, such as stroke, and spinal cord injury.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…Biceps brachii, being a proximal large muscle, is especially important in founding subsequent recovery of the hand in neurologic populations (Kumar et al, 1989). However, based on present findings and previous evidence from our work and of others (Plow et al, 2013; Plow et al, 2014; van Kuijk et al, 2009; Brasil-Neto et al, 1992), it becomes clear that the variable nature of its MEPs renders test-retest measurements of its TMS metrics weakly reproducible. Nevertheless, choosing metrics that define its excitability and output in terms of intensity of TMS device (RMTs or supra-maximal MEP intensities) and/or spatial spread of excitability (COGs and hotspots) would serve as robust markers to longitudinally track recovery and prognosticate upper extremity function across populations, such as stroke, and spinal cord injury.…”
Section: Discussionsupporting
confidence: 69%
“…Our emphasis is novel because proximal muscles are typically less studied than distal owing to the challenge in assaying with TMS. For instance, fewer cortico-motor-neuronal projections that are spread over a relatively wider area (Brasil-Neto et al, 1992), we have recently reported, render their MEPs small and extremely variable (Plow et al, 2013, 2014). Along similar lines, examining reliability of all major metrics is important, because in the study of distal muscles, a divergence is identified, where certain measures are more reliable than others (Malcolm et al, 2006).…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations